Successful live birth after repeated high-dose radiotherapy to the uterus. Issue 4 (April 2021) - Lu, Buo-Jia; Chi, Mau-Shin; Lan, Yen-Po; Chang, Yi-En; Chen, Ching-Hui; Chen, Chi-Huang
Abstract: Research question: It has been established that radiotherapy can increase the risk of adverse pregnancy outcomes. However, there is currently no consensus on the effective sterilizing dose of adulthood uterine radiotherapy. Design: This is a case report of a 36-year-old women with three different cancer types who received repeated high-dose radiotherapy of 66 Gy and 50 Gy to the pelvis. The study used a dose–volume histogram, the most widely used tool to calculate the radiation distribution within a volume of interest in a patient during radiotherapy. It was determined that the current patient's uterus might have received the highest uterine radiation dosage for full-term live birth that has been reported in the current literature. Results: Due to iatrogenic ovarian failure, the woman was only able to use donor eggs. After preparation of the endometrium for 18 days, it had reached 8.7 mm in thickness with a triple-line appearance. Two cleavage-stage embryos were transferred, one of which implanted successfully. The course of the pregnancy was uneventful. Finally, the patient gave birth to a healthy baby via Caesarean section at 38 +5 weeks of gestation. Conclusions: The uterus may be more resistant to radiotherapy than previously understood. Uterine fertility preservation methods should be guided by the age of the patient receiving radiotherapy and the actual dose of radiation exposure of the uterus. Future studies should implement a dose–volume histogram to calculate the radiation exposure of the reproductive organs.